Development of a Systemic Lupus Erythematosus Knowledge Questionnaire: The Relationship Among Disease Proximity, Educational Exposure and Knowledge - (:unkn) unknown (My University, 2016)
There are an estimated 1.5 million people living with systemic lupus erythematosus (SLE), a multisystem autoimmune disorder with a high risk of co-morbid health concerns. The psychological consequences of an SLE diagnosis result in increased daily stress, anticipated stigma, fears of rejection, and increased self-consciousness, all of which can decrease a patient’s quality of life. In order to combat these negative experiences, attempts to increase accurate knowledge of SLE and extinguish SLE misconceptions must be made. The current study aimed to 1) create a medically informed SLE knowledge questionnaire; 2) determine the rate of community members’ SLE knowledge; and 3) determine the relation that disease proximity and educational exposure have on community members’ knowledge of SLE. This novel study is the first to create an SLE knowledge questionnaire and provide evidence that having a closer personal relation to SLE increases SLE knowledge, as does having learned about SLE in an educational setting.
Keywords: Community Knowledge; Disease Knowledge; Disease Proximity; Educational Exposure; Lupus; Questionnaire